2023
DOI: 10.2196/37847
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Overresponsivity and Symptoms Across the Obsessive-Compulsive Spectrum: Web-Based Longitudinal Observational Study

Abstract: Background Sensory overresponsivity (SOR) has emerged as a potential endophenotype in obsessive-compulsive disorder (OCD), but few studies have examined SOR in relation to the major symptom dimensions of OCD and to symptoms across the full obsessive-compulsive (OC) symptom spectrum. Objective This study had 2 main objectives. First, we examined the psychometric properties of the SOR Scales in a community-based sample of Spanish adolescents and adults. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Also, in accordance with our hypotheses, there was a significant positive correlation between obsessive-compulsive symptoms and sensory sensitivity, corroborating previous findings of associations between abnormalities in sensory sensitivity and pediatric as well as adult obsessive-compulsive symptoms [5,[12][13][14][15][16][17][18][19][20][21]. One interpretation of these findings is that children who experience overwhelming sensory input combined with difficulties in accessing the internal states may be at risk of developing obsessive-compulsive behaviors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, in accordance with our hypotheses, there was a significant positive correlation between obsessive-compulsive symptoms and sensory sensitivity, corroborating previous findings of associations between abnormalities in sensory sensitivity and pediatric as well as adult obsessive-compulsive symptoms [5,[12][13][14][15][16][17][18][19][20][21]. One interpretation of these findings is that children who experience overwhelming sensory input combined with difficulties in accessing the internal states may be at risk of developing obsessive-compulsive behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…The present study also aims to explore whether atypical sensory processing is involved in the relation between the access to the internal states and obsessive-compulsive symptoms. Preliminary findings from research with both children and adults with OCD suggest multiple connections between obsessive-compulsive symptoms and atypical sensory processing, sensory over-responsivity, and sensory hypersensitivity [5,[12][13][14][15][16][17][18][19][20][21]. Sensory processing refers to the way in which the nervous system receives, organizes, and deciphers sensory stimuli from internal and external sources [22].…”
Section: Introductionmentioning
confidence: 99%
“…As of now, there is no direct evidence linking this putative genetic continuum to abnormalities of sensory processing. However, a recent study of over 1,400 adolescents and adults, examining the entire spectrum of obsessive-compulsive phenomena, reported that sensory over-responsiveness was associated with this spectrum in a transdiagnostic manner (Moreno-Amador et al, 2023 ). Though requiring replication, this result suggests that the possibility of a genetically influenced neurodevelopmental vulnerability to symptoms across the OC spectrum may be linked to sensory over-sensitivity.…”
Section: Genetics Neurodevelopment and Endophenotypes In Ocdmentioning
confidence: 99%
“…Overall scores for each subscale are calculated separately and range from 0 to 16, with higher scores indicating greater severity. Cronbach alpha outcomes evaluating the internal consistency of the SORS overall and of its subscales indicated strong internal consistency when used in a sample from the United States (SOR-total = 0.93; SOR-hearing = 0.89; SOR-touch = 0.88; SOR-smell = 0.90; SOR-sight = 0.94; SORtaste = 0.88) and in a sample from Spain (hearing = 0.89; touch = 0.86; smell = 0.91; sight = 0.90; taste = 0.86) [30]. -Obsessive-Compulsive Inventory-Revised (OCI-R): The OCI-R is an 18-item self-report questionnaire that assesses obsessive-compulsive symptom severity using a five-point Likert scale ranging from 0 (not at all) to 4 (very much).…”
mentioning
confidence: 99%